Happily ever after ebook Companion to the selection series. - Cass, Kiera (The Selection, 2015)
Go behind the scenes of Kiera Cass's #1 bestselling Selection series with this gorgeous collection of novellas and exclusive extras Meet Prince Maxon before he fell in love with America, and a girl named Amberly before she became queen. See the Selection through the eyes of a guard who watched his first love drift away and a girl who fell for a boy who wasn't the prince. This must-have companion to the Selection series includes all four novellas as well as exclusive bonus content. Includes: The Prince The Guard The Queen The Favorite Exclusive new scenes from The Selection, The Elite, and The One Introductions to each novella from Kiera Cass A map of Illéa and other illustrations And more! Don't miss The Betrothed, a glittering royal romance sure to captivate Kiera Cass's legion of loyal readers and lovers of courtly intrigue alike!